Can performance information motivate citizens to co-produce? - Blom-Hansen, Jens (Politica, 2015)
The article asks what governments can do to motivate citizens to engage in co-production. Based on the broader public administration literature we develop a general explanatory model of citizen co-production motivation. In our empirical study we focus especially on the impact of performance information on citizen co-production motivation. We test our model using data from a randomized survey experiment in which some but not all citizens were presented with information on local government school performance. The analysis shows that performance information influences citizen satisfaction with public school services and in turn also has some but weak impacts on their motivation to co-produce.